Correlation of Thyroid Hormone Derangement with Serum Ferritin Level in Children with Beta Thalassaemia Major at a Tertiary Care Hospital of Bangladesh (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Thalassaemia is a heterogeneous group of disorders. In multi-transfused thalassaemia major patients  the  thyroid  gland  function has  been  reported  to  be  normal,  decreased  reserve,  or  primary hypothyroidism.Objective: This study was an attempt to know the thyroid function status in multi-transfused thalassaemic patients and it's correlation with iron overload.Methods: This cross sectional study was carried out in the Department of Pediatrics at Bangabandhu Sheikh Mujib Medical University (BSMMU) and Transfusion centre of Bangladesh Thalassaemia Samity, Dhaka during May 2011 to April 2012. Previously diagnosed cases of thalassaemia major patients with transfusion dependent at any age with both sexes were randomly selected for this study. Serum total thyroxine (T4), total triiodothyronine (T3), thyroid stimulating hormone (TSH) and serum ferritin level were estimated from venous blood.Results: A total of 50 previously diagnosed cases of thalassaemia major patients of which 30 male and 20 female of 4 to 15 years age, transfusion dependent were randomly selected for this study. Hypothyroidism was present in 10(20%) patients.  Among  these 10 patients  compensated  primary  hypothyroidism  was  in  5(10%)  cases  and decompensate primary hypothyroidism was 5(10%) cases. The TSH value of hypothyroid patients was higher. Serum ferritin value was significantly higher in all the three groups of thalassaemic patients. There was no significant correlation between the high serum ferritin value with thyroid stimulating hormone or serum total thyroxin level.Conclusion: All transfusion dependent thalassaemic patients need periodic evaluation of thyroid  function  because  there  was  incidence  of  hypothyroidism.DOI: http://dx.doi.org/10.3329/jssmc.v5i2.20762J  Shaheed  Suhrawardy  Med  Coll 2013;5(2):87-90]